Bone cement and cementation technique, antibiotics and bone cement spacers: what should you know? - Calonego, Giovanni (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Analyzed cementing technique and implant design . It is shown that scientific and technological progress in the industry enables us to obtain 97% survival rate of implants 10 years after surgery. According to recent reports , infectious complications in 20% of cases the cause of revision cases . Using acrylic cement saturated antibiotics reduces the risk of infectious complications. Cement spacers allow to obtain a positive result in the case of chronic infection.